2020
DOI: 10.14569/ijacsa.2020.0111080
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Common and Uncommon Tones by P300 Feature Extraction and Identification of Accurate P300 Wave by Machine Learning Algorithms

Abstract: An event-related potential (ERP) is a measure of brain response to a specific sensory, cognitive, or motor event. One common ERP technique used in cognition research is the oddball paradigm where the brain's response to common and uncommon stimuli is compared. The neurologic response to the oddball paradigm produces a P300 ERP which is one of the major visual/auditory sensory ERP components. The purpose of this study to classify ERP responses to common and uncommon tones by extracting the P300 feature from ERP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Although the study applied deeplearning techniques, the performance of the current study where EROs in the time-frequency domain were used as features in the 'traditional' machine learning approach was much better than in this study where only time-domain features were used. Moreover, in the current study, the preprocessing step that makes the data more suitable for ML (Akhter et al, 2020) was more comprehensive than in the study by Aellen et al (2021).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although the study applied deeplearning techniques, the performance of the current study where EROs in the time-frequency domain were used as features in the 'traditional' machine learning approach was much better than in this study where only time-domain features were used. Moreover, in the current study, the preprocessing step that makes the data more suitable for ML (Akhter et al, 2020) was more comprehensive than in the study by Aellen et al (2021).…”
Section: Discussionmentioning
confidence: 85%
“…Among the different features of EEG data used in the literature, ERO in the Time-Frequency domain provides more information about temporal, spectral, and spatial dynamics of cognitive processes (Aliakbaryhosseinabadi, Kamavuako, Jiang, Farina, & Mrachacz-Kersting, 2019). However, various studies showed that ERP features also had promising classification performances for stimuli classification (Parvar et al, 2014;Tjandrasa & Djanali, 2018;Akhter, Lawal, Tanvir, & Ahmed, 2020;Borra & Magosso, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It has been established by different studies that ERP gives a maximum positive peak of around 300 ms-600 ms and the peak is higher for target/oddball stimuli compared with standard stimuli. This component is known as the P300 component [7].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis and analysis of schizophrenic patients can be done through the use of electroencephalogram (EEG) signals [9], [10]. The EEG signals have unique characteristics, variability, and dimensionality [11] as they can provide information about the electrical activities of a human brain [12], [13], and also they have the great potential to predict whether a person is a healthy control or schizophrenic [14]- [16]. In the medical field, EEG signals have vast applications like it can be used to detect epilepsy, comma, clinical death, and schizophrenia [17].…”
Section: Introductionmentioning
confidence: 99%